Analysis of Factors Affecting Labor Productivity in the Bamboo Handicraft Industry in Loyok Village, Sikur District, East Lombok Regency - Siskawati, Siskawati; Fuady, Helmy; Yuniarti , Titi (West Science Journal Economic and Entrepreneurship, 2024)
This study aims to analyze the influence of age, work experience and the number of family dependents partially and simultaneously on labor productivity in the bamboo handicraft industry in Loyok Village, Sikur District, East Lombok Regency. The type of research used in this study is an explanatory quantitative method with a sampling of 56 people with a population of 126 people. The data obtained by distributing questionnaires and sampling this study used simple random sampling. The results of the analysis show that partially of the three variables used in this study, there are two variables that have an influence and significance, namely age with a significant value of 0.009 < 0.05 and work experience with a significant value of 0.021< 0.05 while for the variable the number of family dependents with a significant value of 0.051< 0.05 has an insignificant effect on labor productivity in the bamboo handicraft industry in Loyok Village. Meanwhile, simultaneously that together, the independent variable X affects labor productivity with a significant value of 0.006 < 0.05. Meanwhile, the R2 Adjusted R Square value shows that all independent variables are able to explain the dependent variable by 16.4% and the remaining 83.6% are explained by other variables that are not included in this study.